A case study of the wastewater treatment system modification in denim textile industry. Issue 10 (3rd October 2021) - Zhang, Li; Lei, Ming; Feng, Te; Chang, William; Ye, Alice; Yi, Hong; Yi, Changhai
Abstract: Jeanswear becomes more and more popular all over the world. However, a large amount of non-biodegradable and environmentally harmful wastewater is produced during the jeanswear production. Therefore, developing an effective system for the wastewater treatment in the denim textile industry is of great significance. During the last ten years, our lab has always focused on the clean production and smart manufacturing in the denim textile industry, especially the jeanswear production chain. In this work, we studied and modified the denim textile wastewater treatment system from a sewage treatment plant in the Guangdong province of China. Based on the existed wastewater treatment system, we improved the system by using the membrane bioreactor (MBR) system and reverse osmosis membrane (ROM) technology. The effluent quality parameters meet the water quality discharge standard in the 'Discharge standards of water pollutants for dyeing and finishing of the textile industry'. Besides, the reuse ability of the treated wastewater has no obvious difference from the tap-water. Now, the modification of the wastewater treatment system is ongoing in the Zhongshan Yida company based on the results in this work.